Web and wireless geographical information systems : 16th International Symposium, W2GIS 2018, A Coruña, Spain, May 21-22, 2018, Proceedings /: 16th International Symposium, W2GIS 2018, A Coruña, Spain, May 21-22, 2018, Proceedings. (2018) - Unknown
No abstract available